First observation of a baryonic B+c decay - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Physical review letters, 2014)
A baryonic decay of the B+c meson, B+c→J/ψp¯pπ+, is observed for the first time, with a significance of 7.3 standard deviations, in pp collision data collected with the LHCb detector and corresponding to an integrated luminosity of 3.0 fb−1 taken at center-of-mass energies of 7 and 8 TeV. With the B+c→J/ψπ+ decay as the normalization channel, the ratio of branching fractions is measured to be B(B+c→J/ψp¯pπ+)/B(B+c→J/ψπ+)=0.143+0.039−0.034(stat)±0.013(syst). The mass of the B+c meson is determined as M(B+c)=6274.0±1.8(stat)±0.4(syst) MeV/c2, using the B+c→J/ψp¯pπ+ channel.